회전날개형 비행체의 확장현실 과학 시뮬레이션을 위한 고속·고정밀 유동 해석 및 가시화 모듈 개발 - 박상진(Sang-Jin Park); 박현솔(Hyun-Sol Park); 황원태(Won-Tae Hwang); 신정훈(Jung-Hun Shin); 최성임(Seong-Im Choi); 김민아(Min-Ah Kim) (한국CDE학회 논문집, 2024)
Physical simulation in virtual reality has been widely used in the game/film/media industry. Recently, as convergence with physical space has occurred, it has been replaced by the terms extended reality or mixed reality, and is expanding into industrial fields that require digital twins. Previously, users in extended reality field have utilized high-speed, low-accuracy flow simulations such as SPH, but as industrial and research applications are considered, need to execute high-precision, high-speed flow simulations required for simulation digital twins in the reality space has emerged. In this study, we developed extended reality-based scientific simulation and visualization modules related to various aircrafts such as delivery drone and UAM. The simulation module was developed so that it runs high-precision eddy particle simulations capable of analyzing turbulence-based rotor-wall interaction on a server. Next the visualization module renders the results on headset devices such as Hololens 2. This research employed a vortex particle method for accurate and fast fluid flow simulation, and developed mobile visualization pipeline with Unity3D renderer and web protocol. Using a particle simulator named ‘FLOWUnsteady’, it was considered to score at least 75% accuracy for bearable content play speed. This study showed that such heavy simulation as industry-level unsteady fluid flow can be performed in immersive extended reality space. In the future condition of higher computational and network capacity, the developed simulation modules will be combined with other extended reality interactions like gesture and haptic for better experiences on content applications. KCI Citation Count: 0